EFEKTIVITAS INFUSA KULIT NANAS SEBAGAI BIOLARVASIDA Aedes aegypti - Liah Kodariah; ally Kafesa (Jurnal Kesehatan Rajawali, 2021)
Dengue hemorrhagic fever is a disease caused by the dengue virus which is transmitted through the bite of the Aedes aegypti mosquito. Controls are generally carried out chemically which can cause negative impacts if used continuously. Pineapple peel is a plant that can be used as a biolarvicide which contains flavonoids, saponins, tannins, and bromelain enzymes which can cause the death of Aedes aegypti larvae.This study aims to determine the concentration of pineapple peel infusion which is effective in killing Aedes aegypti larvae seen from the LC50 value.This research uses experimental methods. The sample population was larvae of Aedes aegypti. Samples were taken in the captivity of the Bandung Health Polytechnic Laboratory as many as 140 instar III Aedes aegypti larvae with purposive sampling technique. The concentration of pineapple skin infusion used was 23%, 21%, 20%, 19%, and 17%. each treatment In this study, the percentage of larvae mortality was obtained, namely at a concentration of 23% there were 65% of larvae deaths, at a concentration of 21% there were 60% deaths, at a concentration of 20% there were 50% deaths, at a concentration of 19% there were 50% deaths, and at a concentration of 20% there were 50% deaths. and at concentration of 17% contained 35% of deaths.Based on the research, it can be concluded that pineapple skin infusion can be used as an effective biolarvicide seen from the LC50 value, which is at a concentration of 19%. contained 10 test larvae with two repetitions and observed after 24 hours.